Does Government Oversight Improve Access to Nursing Home Care? Longitudinal Evidence From US Counties - Larry L. Howard PhD (SAGE Publishing, 2014)
Gains in life expectancy around the world have increasingly placed pressure on governments to ensure that the elderly receive assistance with activities of daily living. This research examines the impact of government oversight of Medicaid payment policies on access to nursing home care services in the United States. Variation in price levels induced by a federal policy shift in 1997 is used to identify the effect of Medicaid reimbursements on the number of nursing homes and beds available. Court rulings prior to the policy change are used to categorically define a range of oversight treatments at the state level. Difference-in-differences estimates indicate a significant decline in access to nursing home care services for individuals living in states in which courts consistently ruled that Medicaid reimbursements did not meet the minimum standard implied by federal law. The findings suggest that nursing home care services were made more accessible through a combination of legislative and judicial oversight of Medicaid payment policies.